Impaired cognition in depression and Alzheimer (AD): a gradient from depression to depression in AD - Narahyana Bom de Araujo; Helena Sales Moraes; Heitor Silveira; Cynthia Arcoverde; Paulo Eduardo Vasques; Maria Lage Barca; Anne-Brita Knapskog; Knut Engedal; Evandro Silva Freire Coutinho; Andrea Camaz Deslandes; Jerson Laks (Arquivos de Neuro-Psiquiatria)
Objective To assess cognition in major depressed (MD), Alzheimer's disease (AD), and depression in AD elderly. Method Subjects were evaluated by Mini Mental, Rey Auditory Verbal Learning Test, Rey Complex Figure, Digit Span, Similarities, Trail Making A/B, Verbal Fluency and Stroop. One-way ANOVA and multivariate models were used to compare the performance of each group on neuropsychological tests. Results We evaluated 212 subjects. Compared to MD, attention, working memory, processing speed and recall showed significantly better in controls. Controls showed significantly higher performance in all cognitive measures, except in attention compared to AD. Verbal fluency, memory, processing speed and abstract reasoning in MD was significantly higher compared to AD. AD was significantly better in general cognitive state than depression in AD. All other cognitive domains were similar. Conclusion A decreasing gradient in cognition appeared from the control to depression in AD, with MD and AD in an intermediate position.